2013
DOI: 10.1186/2191-1991-3-25
|View full text |Cite
|
Sign up to set email alerts
|

Does overcrowding and health insurance type impact patient outcomes in emergency departments?

Abstract: We examine the impact of Emergency Department (ED) overcrowding on wait times and patient outcomes using a unique cross section of about 32,000 patients for an ED located in the Southwestern United States. We construct a measure of a patient’s outcome and estimate the extent to which it is worsened by long waits in the ED. We find that waiting at an ED due to overcrowding tends to generate a negative outcome for all patients. We also find that this negative outcome is larger for those on Medicaid or who have n… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
5
0

Year Published

2014
2014
2022
2022

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 13 publications
(5 citation statements)
references
References 21 publications
0
5
0
Order By: Relevance
“…They are older, more often male, and their visits tend to result in a higher rate of hospitalization [6]. A tendency toward inappropriate ED use by homeless patients is documented in the literature in association with ED overcrowding resulting in negative prognostic outcomes [7,8].…”
Section: Introductionmentioning
confidence: 99%
“…They are older, more often male, and their visits tend to result in a higher rate of hospitalization [6]. A tendency toward inappropriate ED use by homeless patients is documented in the literature in association with ED overcrowding resulting in negative prognostic outcomes [7,8].…”
Section: Introductionmentioning
confidence: 99%
“…[6][7][8] As ED utilization rises, research on the effects of crowding has primarily focused on its influence on patient outcomes, including treatment delays [9][10][11] and patient mortality. [12][13][14][15] Less well characterized are organizational responses to increasing operational pressure, such as changes to rates of admission.…”
mentioning
confidence: 99%
“…11 Similarly, studies have shown that wait times for uninsured patients can be as high as 33% longer than wait times for patients with insurance. 29 There are several possible explanations for the race- and insurance-related disparities in ED wait times. First, efficient and effective EDs (higher-quality EDs) may be less accessible to vulnerable populations since minority patients tend to reside closer to low-quality hospitals, as defined by mortality rate, relative to their White counterparts.…”
Section: Discussionmentioning
confidence: 99%